N6-Methylandenosine-Related lncRNAs Are Potential Biomarkers for Predicting the Overall Survival of Lower-Grade Glioma Patients - Tu, Zewei; Wu, Lei; Wang, Peng; Hu, Qing; Tao, Chuming; Li, Kuangxun; Huang, Kai; Zhu, Xingen (Frontiers in Cell and Developmental Biology, 2020)
The prognostic value of N6-methylandenosine-related long non-coding RNAs (m6A-related lncRNAs) was investigated in 646 lower-grade glioma (LGG) samples in The Cancer Genome Atlas (TCGA) and the Chinese Glioma Genome Atlas (CGGA) datasets. We implemented Pearson correlation analysis to explore the m6A-related lncRNAs, and then univariate Cox regression analysis was performed to screen their prognostic roles. Twenty-four prognostic m6A-related lncRNAs were identified and inputted in a least absolute shrinkage and selection operator (LASSO) Cox regression to establish a m6A-related lncRNA prognostic signature (m6A-LPS) in the TCGA dataset. Corresponding patient risk scores were calculated and divided LGG patients into low- and high-risk subgroups by the value of median risk scores. The m6A-LPS was validated in the CGGA dataset and it showed a robust prognostic ability in the stratification analysis. Principal component analysis showed that the low- and high-risk subgroups had distinct m6A status. Enrichment analysis indicated that malignancy-associated biological processes, pathways and hallmarks were more common in the high-risk subgroup. Moreover, we constructed a nomogram (based on m6A-LPS, age and World Health Organization grade) that had a strong ability to forecast the overall survival (OS) of the LGG patients in both datasets. Besides, we also establish a competing endogenous RNA (ceRNA) network on the strength of seven of the twenty-four m6A-related lncRNAs.